LE TÉLÉAPPRENTISSAGE DANS L’ENSEIGNEMENT UNIVERSITAIRE : AVANT ET APRÈS LA PANDÉMIE - Widła, Halina (Neofilolog, 2021)
At the end of the first semester of the 2019/2020 academic year, we conducted an opinion survey of 50 philology students on their willingness to adopt new pedagogical approaches based largely on digital media. We measured the degree of appreciation of different forms of academic work, including lectures, tutorials and seminars, modified by these approaches. After a year of the COVID-19 pandemic, we investigated the potential revision of views on the practical application of the innovations described in 2020. Our research focused on appreciating the usefulness and effectiveness of the teaching methods analyzed during the initial research, judged through the prism of current experiences.